Metabolic Perturbations and Severe COVID-19 Disease: Implication of Molecular Pathways - Ersilia Nigro; Fabio Perrotta; Rita Polito; Vito D’Agnano; Filippo Scialò; Andrea Bianco; Aurora Daniele (International Journal of Endocrinology)
Coronavirus disease (COVID-19) is caused by SARS-CoV-2 virus, which can result in serious respiratory illnesses such as pneumonia leading to respiratory failure. It was first reported in Wuhan, Hubei, China, in December 2019 and rapidly spread globally, becoming a pandemic in March 2020. Among comorbidities observed in SARS-CoV-2 positive patients, hypertension (68.3%) and type 2-diabetes (30.1%) are the most frequent conditions. Although symptoms are highly heterogeneous (ranging from absence of symptoms to severe acute respiratory failure), patients with metabolic-associated diseases often experience worse COVID-19 outcomes. This review investigates the association between metabolic disorders and COVID-19 severity, exploring the molecular mechanisms potentially underlying this relationship and those that are responsible for more severe COVID-19 outcomes. In addition, the role of the main biological processes that may connect metabolic alterations to SARS-CoV-2 infection such as hyperglycemia, immune system deregulation, ACE-2 receptor modulation, and inflammatory response is described. The impact of metabolic disorders on the prognosis of COVID-19 has major implications in public health especially for countries affected by a high incidence of metabolic diseases.